Koncentryczność. Wieczność miasta w świetle semiotyki kultury - Machtyl, Katarzyna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
There are two ways of considering the eternity presented in this paper: the eternity as a fundamental value, in the context of sacrum, and the eternity expressed as a temporal phenomenon. The author collates linguistic and semiotic view with the ontological and metaphysical one. The text is built on two axes: theoretical and methodological optic founded by authors representing Tartu-Moscow Semiotic Group on the one hand, and the metaphysical way of describing the presence. There is one notion that combines these two approaches: the centre. The text presents characteristic relations betweencultural system and its centre (centres), as well as the centre as a place of presenceand sense (according to the Western metaphysics) or, in contrary, as a “sacred nothing” (according to the Eastern metaphysics). The last part of the article discusses some Old Testament texts presenting Babylon and Jerusalem. Author refers mainly to the conceptsof Lotman, Toporow, Barthes and Derrida.